Impact of Oxytocin Massage for Postpartum Mothers on Breast Milk Production - Umamity, Syafitrah; Fitriasari, Endah Fitriasari; Umasugi, Muhammad Taufan (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Introduction Mother's Milk is a divine gift explained in the Quran, Surah Lukman verse 14, which recommends mothers to breastfeed their children for a full two years. Breast milk is considered the best source of nutrition for infants, especially within the age range of 0–6 months. However, not all breastfeeding mothers can easily produce breast milk directly, as the process involves a complex interaction influenced by the hormone oxytocin. This study aims to assess the impact of applying oxytocin massage on breast milk production in postpartum mothers in the Working Area of Waimital Community Health Center, Kairatu District, West Seram Regency. The research design used is quasi-experimental, with sample selection using non-probability sampling involving 20 respondents. The research instrument used a questionnaire, and data analysis was conducted using the Mann-Whitney test and Wilcoxon test to evaluate changes before and after the intervention for each variable. The bivariate analysis results based on the treatment group variable showed the highest P-value at 0.008 and the lowest at 0.003 (< 0.05), while in the control group, the highest P-value was 0.157 and the lowest was 0.083 (< 0.05). Thus, it can be concluded that the application of oxytocin massage has a highly significant effect on breast milk production in postpartum mothers in the treatment group.